Association of mineral content outside of bone with coronary artery calcium and 1‐year cardiovascular prognosis in maintenance hemodialysis patients. Issue 10 (25th April 2019) - Xiong, Yuqin; Li, Jiameng; Sun, Si; Han, Mei; Liao, Ruoxi; Li, Yupei; Wang, Liya; Lin, Liping; Liu, Qiang; Su, Baihai
Abstract: Coronary artery calcifications (CACs) are common among maintenance hemodialysis (MHD) patients and associated with increased morbidity and mortality due to cardiovascular events. The insight into chronic kidney disease‐mineral and bone disorder (CKD‐MBD) established a correlation between dysregulated mineral metabolism and CACs. This study aimed to identify the association of mineral content outside of bone (MCOB) with CACs and cardiovascular events in MHD patients. In the pilot prospective study with no intervention, patients underwent body composition assessment by body composition monitor after hemodialysis and computed tomography examination using the Agatston scoring method simultaneously within a week. The primary end point included cardiovascular events and cardiovascular death. Correlations and receiver operating characteristic analysis elucidated the associations of MCOB with CACs; multivariate analysis assessed the cardiovascular risk for groups with different MCOB. One hundred three eligible patients with an average age of 48 (35‐63) years old were enrolled and followed up to 12 (11‐12.5) months, among which 52.4% had detectable CACs at baseline. MCOB showed an inverse correlation with Agatston score and significantly discriminated the patients with Agatston score > 0 (AUC = 0.737; P < 0.001) and 400 (AUC = 0.733; P < 0.001). MCOB ≤ 9.2657 mg/kg was an independent risk factor for CACs (OR = 4.853; P = 0.044) and strong predictor for cardiovascular morbidity and mortality (HR = 10.108; P = 0.042), as well as rehospitalization (HR = 2.689; P = 0.004). MCOB inversely correlated with the presence and extent of CACs, and could discriminate Agatston score > 0 and 400, which also presented as an independent indicator for CKD‐MBD and 1‐year cardiovascular prognosis in adult MHD patients. Additional studies are required for identifying this issue.